Genome-scale flux balance analysis reveals redox trade-offs in the metabolism of the thermoacidophile Methylacidiphilum fumariolicum under auto-, hetero-and methanotrophic conditions - Saldivar, Alexis; Ruiz-Ruiz, Patricia; Revah, Sergio; Zuñiga, Cristal (Frontiers in Systems Biology, 2024)
Members of the genus Methylacidiphilum are thermoacidophile methanotrophs with optimal growth temperatures between 50°C and 60°C, and pH between 1.0 and 3.0. These microorganisms, as well as other extremophile bacteria, offer an attractive platform for environmental and industrial biotechnology because of their robust operating conditions and capacity to grow using low-cost substrates. In this study, we isolated Methylacidiphilum fumariolicum str. Pic from a crater lake located in the state of Chiapas, Mexico. We sequenced the genome and built a genome-scale metabolic model. The manually curated model contains 667 metabolites, 729 reactions, and 473 genes. Predicted flux distributions using flux balance analysis identified changes in redox trade-offs under methanotrophic and autotrophic conditions (H2+CO2). This was also predicted under heterotrophic conditions (acetone, isopropanol, and propane). Model validation was performed by testing the capacity of the strains to grow using four substrates: CH4, acetone, isopropanol, and LP-Gas. The results suggest that the metabolism of M. fumariolicum str. Pic is limited by the regeneration of redox equivalents such as NAD(P)H and reduced cytochromes.